Miss World Meets the Pan Men - Jacobs, Carl (Trinidad Guardian)
At the first major show in the Queen's Park Savannah, Miss World, Miss Carol Joan Crawford of Jamaica will mingle with steelbandsmen and the United States Marines in "Carnival Panorama". Miss Crawford will present the Panorama Steelband Champion with a silver cup and in turn, she will be presented with a full size tenor pan mounted on a stand as a gift.
Keywords: Beauty contestants -- Jamaica; Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago -- History; Panorama (Musical festival)